b-Ionone Modulates the Expression of miRNAs and Genes Involved in the Metastatic Phenotype of Microdissected Persistent Preneoplastic Lesions in Rats Submitted to Hepatocarcinogenesis - Silva Furtado, Kelly (2016)
MicroRNAs (miRNAs) are post-transcriptional gene expression regulators which expression is frequently altered in hepatocellular carcinoma (HCC). b-ionone (bI) is noted for its ability to inhibit persistent preneoplastic lesions (pPNLs) in liver rats. We evaluated the expression of miRNAs involved in carcinogenesis and possible targets modulated by bI, in pPNLs and surrounding of microdissected tissues. Rats subjected to resistant hepatocyte model were treated during promotion stage with bI (16 mg/100 g body weight) or corn oil (CO; 0.25 mL/100 g body weight; controls). Five animals receive no treatment (NT). In CO group, 38 and 29 miRNAs showed reduced expression relative to NT (P < 0.05) in pPNLs and surrounding, respectively. No miRNAs showed increased expression in surrounding of the CO compared to NT group; however, 30 miRNAs showed increased expression (P 0.05) in pPNLs of the CO group. There was no difference between bI and CO groups (P > 0.05) in the expression of miRNAs in surrounding. In pPNLs bI increased expression of miR-122 and miR-34a (P 0.05) and reduced of Igf2 (P 0.05), target of the latter, compared to CO. Additionally, bI decreased the expression of miR-181c and its target Gdf2 (P 0.05). bI reduced the expression of miR-181b and miR-708 (P 0.05) and increased the expression of their respective target mRNAs Timp3 and Mtss1 (P 0.05), relative to CO group. Modulation of miRNAs target genes by bI was confirmed in vitro. bI is a promising chemopreventive agent in the initial stages of hepatocarcinogenesis, as it modulates the expression of the miRNAs and target genes that can alter the metastatic phenotype of HCC.